2009
DOI: 10.1523/jneurosci.1951-09.2009
|View full text |Cite
|
Sign up to set email alerts
|

Get Aroused and Be Stronger: Emotional Facilitation of Physical Effort in the Human Brain

Abstract: Effort magnitude is commonly thought to reflect motivation, but little is known about the influence of emotional factors. Here, we manipulated the emotional state of subjects, via the presentation of pictures, before they exerted physical effort to win money. After highly arousing pictures, subjects produced more force and reported lower effort sensation, regardless of monetary incentives. Functional neuroimaging revealed that emotional arousal, as indexed by postscan ratings, specifically correlated with bila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
89
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(102 citation statements)
references
References 48 publications
10
89
3
Order By: Relevance
“…Although an emotion driven increase in force production has been shown previously, participants in these studies were required to produce force at moderate or high levels (Coombes et al, 2008;Schmidt et at., 2009). The current findings, therefore, demonstrate that although low, moderate, and high tone levels may rely on varying neural circuits (Ehrsson et al, 2001;Spraker et al, 2007), the effect of emotion on these circuits remains fundamentally similar.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although an emotion driven increase in force production has been shown previously, participants in these studies were required to produce force at moderate or high levels (Coombes et al, 2008;Schmidt et at., 2009). The current findings, therefore, demonstrate that although low, moderate, and high tone levels may rely on varying neural circuits (Ehrsson et al, 2001;Spraker et al, 2007), the effect of emotion on these circuits remains fundamentally similar.…”
Section: Discussionmentioning
confidence: 99%
“…Also, there is no evidence that pairing emotion and motor processes alters the typical pattern of emotional reactivity demonstrated when passively viewing emotional images (Coombes, Janelle, & Duley, 2005;Schmidt et at., 2009). Future research efforts are needed to (a) qualify these findings in healthy and clinical samples across the lifespan (Christou et al, 2004), (b) investigate the cortical and subcortical neural circuits that underlie the interaction between emotion and movement (Borsook, 2007;Coombes, Tandonnet et al, 2009;Hajcak et al, 2007;Pessiglione et al, 2007;Schmidt et al, 2009;van Loon et al, 2010), and (c) examine the implications of emotion-induced changes in movement in a variety of performance settings (Woodman et al, 2009). In conclusion, wexposure to emotional images impacts the accuracy but not variability of a sustained low-level force contraction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have also shown that positively valenced stimuli facilitate motor behaviour by acting as a source of motivation, including enhanced force output by pleasant emotional images (Coombes et al, 2008;Coombes et al, 2011;Naugle et al, 2010) and monetary reward (Pessiglione et al 2007;Schmidt et al 2009;Schmidt et al 2012). Conversely, negative affect can diminish goal priming effects and motivation (Aarts et al, 2007).…”
Section: Introductionmentioning
confidence: 98%
“…Given that emotions may be associated with different action tendencies (Frijda 2009), it is plausible emotional valence (i.e., positive or negative affect) itself conveys information related to action and inaction representations, which might influence goal pursuit and motor performance in different ways. Emotional arousal (i.e., the 'intensity' of psychological and physiological alertness) also modulates motor behaviour; for instance, greater force output is produced in response to high relative to low arousing emotional stimuli (Coombes et al, 2008;Schmidt et al, 2009). However, how emotional processes modulate the activation of action representations and subsequent behaviour remains poorly understood.…”
Section: Introductionmentioning
confidence: 99%